2007
DOI: 10.1007/s10350-007-0217-6
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Dysplasia in Ileal Pelvic Pouches After Restorative Proctocolectomy

Abstract: Clinical and microscopic evidence of ileal-pouch inflammation is common. Ileal-pouch mucosal dysplasia is uncommon, occurring in only 1 of 138 patients. Villous atrophy and colonic metaplasia were not observed in this series. Routine pouch surveillance with biopsies may not be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 46 publications
1
17
0
2
Order By: Relevance
“…Th e development of dysplasia or adenocarcinoma in pouches is very infrequent ( 356,357 ). Risk factors for dysplasia include long duration of UC before proctocolectomy, chronic pouchitis, PSC, and dysplasia or adenocarcinoma in the colectomy specimen ( 356,358,359 ).…”
Section: Recommendations For the Management Of Pouchitismentioning
confidence: 99%
“…Th e development of dysplasia or adenocarcinoma in pouches is very infrequent ( 356,357 ). Risk factors for dysplasia include long duration of UC before proctocolectomy, chronic pouchitis, PSC, and dysplasia or adenocarcinoma in the colectomy specimen ( 356,358,359 ).…”
Section: Recommendations For the Management Of Pouchitismentioning
confidence: 99%
“…44,45 These numbers imply the idea that the development of adenomas is accelerated in the ileal pouch of patients with FAP, 46 although others found that mucosal dysplasia is uncommon. 47 Furthermore, the description of less than 10 pouch adenocarcinomas so far 9,10,48,49 may indicate that RPC does not eliminate the risk of malignization. So, the tradeoff of neoplasia control in FAP patients seems to be much more complex than previously thought.…”
Section: Discussionmentioning
confidence: 97%
“…In a cross-sectional study of 128 IPAA patients with underlying IBD, one patient with IND had no dysplasia on subsequent surveillance biopsy. 26 In a separate study of 113 cases, one patient had IND on two consecutive endoscopy biopsies and no dysplasia or IND was found in a subsequent endoscopic biopsy. 27 On the other hand, IND may "progress".…”
Section: Discussionmentioning
confidence: 97%